2009
DOI: 10.3109/07420520903385564
|View full text |Cite
|
Sign up to set email alerts
|

AGE-DEPENDENT ALTERATIONS IN HUMANPER2LEVELS AFTER EARLY MORNING BLUE LIGHT EXPOSURE

Abstract: In our modern society, we are exposed to different artificial light sources that could potentially lead to disturbances of circadian rhythms and, hence, represent a risk for health and welfare. Investigating the acute impact of light on clock-gene expression may thus help us to better understand the mechanisms underlying disorders rooted in the circadian system. Here, we show an overall significant reduction in PER2 expression in oral mucosa with aging in the morning, noon, and afternoon. In the afternoon, 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
3
17
1
Order By: Relevance
“…This observation seems to stand in contrast to the findings of previous studies, which observed measurable effects of blue light on CRY1, BMAL [34], PER2 [31, 32], and PER3 [53] expression. However, of these four studies, only one examined the independent effect of morning blue light exposure, but in buccal mucosa and not peripheral blood.…”
Section: Discussioncontrasting
confidence: 99%
“…This observation seems to stand in contrast to the findings of previous studies, which observed measurable effects of blue light on CRY1, BMAL [34], PER2 [31, 32], and PER3 [53] expression. However, of these four studies, only one examined the independent effect of morning blue light exposure, but in buccal mucosa and not peripheral blood.…”
Section: Discussioncontrasting
confidence: 99%
“…It is worth noting that our sample was slightly younger than that of previous studies showing agerelated differences in nonvisual effects of light (61 years on average in our sample v. 65.8 years [Jud et al, 2009;Sletten et al, 2009] or 68.3 years [Duffy et al, 2007]). However, such small age differences appear unlikely to fully explain the very limited effect of aging on steady-state PLR in our data compared to that of other studies.…”
Section: Discussionmentioning
confidence: 48%
“…Indeed, the impact of light on the circadian phase, and therefore on circadian entrainment, seems to diminish with aging (significant impact found in Duffy et al [2007] but not in Sletten et al [2009]). Recent evidence also suggests that acute effects of light such as melatonin suppression, subjective alertness enhancement, and induction of PERIOD2 expression decrease with age for blue but not for green light (Herljevic et al, 2005;Jud et al, 2009;Sletten et al, 2009). However, age-related alterations in the impact of light on pupil light reflex (PLR) that regulates the amount of light reaching the retina remain poorly understood.…”
mentioning
confidence: 99%
“…Rhythmic changes with a period of approximately 24 h are defined circadian (Edery 2000;Duguay and Cermakian 2009;Lemmer 2009;Mazzoccoli 2011). Circadian rhythmicity is driven by a timing clockwork composed of a central clock, located in the hypothalamic suprachiasmatic nuclei (SCN), which responds to external lighting cues and in turn drive self-sustained clocks in all peripheral tissues via neuro-humoral circadian output pathways (Lowrey and Takahashi 2000;Hastings et al 2003;Schibler and Sassone-Corsi 2002;Dardente and Cermakian 2007;Jud et al 2009;Koch et al 2009;Schwimmer et al 2010;Erren et al 2011;Yamamura et al 2010). At a subcellular and molecular level, the central and peripheral clocks are operated by feedback loops of circadian genes, including ARNTL (BMAL1) and its paralog ARNTL2 (BMAL2), CLOCK, PERIOD (PER1-3), and CRYPTOCHROME (CRY1 and 2), with the phosphorylation activity of casein kinase I d/e.…”
Section: Introductionmentioning
confidence: 99%